ISSUES OF APPLICATION OF BUSINESS MANAGEMENT MODELS IN INDUSTRIAL ENTERPRISES - Avulchaeva Feruza Dzhurakuzievna (Scholars Digest Publishing, 2024)
The article describes the essence of business models, their classification, the processes of applying business models in industrial enterprises. Also, the main approaches of foreign scientists to business models are presented. Proposals are given on the prospects of applying business models.
Keywords: industrial enterprises, business models, approaches, classification of models, division of powers, stages, process description.